Relative dispersion of heavy metals in the upper basin of the Torres – Vizcarra river, Ancash and Huanuco deparments - Chira Fernández, Jorge (2011)
With the sample of stream sediments in the basin of the river Torres – Vizcarra (Huanuco-Ancash), which have been subjected to the chemical speciation method, it has been possible to define the dispersion process for the main metallic elements. This characterization is define by the relation between the total metal content and the residual content of the sample, giving as a result a factor named relative dispersion, which it has been determined for the main elements, highlighting among them, copper, lead, zinc and cadmium because of its very high mobility, while chromium and vanadium for its low mobility. The application of the sequential extraction technique allows defining the fraction of metallic elements moving in a specific environment, identifying the bioavailable fractions, as well as allows identifying the real environmental impact produced by the dispersion of heavy metals in sediments.